An analysis of the off-campus internship program of Cebu Normal College its implications for the Nakornpathom Teachers College, Thailand - Manee-rat, Somchai 1934-
The respondents include the supervisor and assistant supervisor of student-teaching, teacher-training instructors, cooperating teachers, and student teachers during the first semester of the school year 1974-1975. Twenty-three instructional and 3 related non-instructional activities are performed. Three important problems identified by supervisors are reluctance and incompetence of cooperating teachers and choice of cooperating schools. The student teachers' important problems are maintaining discipline, inadequacy of instructional materials, language difficulties, rigid and autocratic supervision, preparation of audio-visual materials, and inadequacy of classroom facilities.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Cebu Normal College; Nakornpathom Teachers College, Thailand; Student teaching -- Philippines